2018
DOI: 10.1111/eth.12826
|View full text |Cite
|
Sign up to set email alerts
|

Antipredator behaviour of invasive geckos in response to chemical cues from snakes

Abstract: Antipredator behaviours and the ability to appropriately assess predation risk contribute to increased fitness. Predator avoidance can be costly; however, so we expect prey to most strongly avoid predators that pose the greatest risk (i.e., prey should show threat sensitivity). For invasive species, effectively assessing the relative risk posed by predators in the new environment may help them establish in new environments. We examined the antipredator behaviour of introduced Asian house geckos, Hemidactylus f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The ability to distinguish between predators and nonpredators and risk levels have been found in reptile and primate species (Buchanan- Smith et al 1993;Stapley 2003;Lloyd et al 2009;Cisterne et al 2014;Cornelis et al 2019). The pygmy salamander (Desmognathus wrighti) could distinguish between chemical cues from a specialist snake predator and two generalist predators, namely, beetle and salamander species (Forester et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to distinguish between predators and nonpredators and risk levels have been found in reptile and primate species (Buchanan- Smith et al 1993;Stapley 2003;Lloyd et al 2009;Cisterne et al 2014;Cornelis et al 2019). The pygmy salamander (Desmognathus wrighti) could distinguish between chemical cues from a specialist snake predator and two generalist predators, namely, beetle and salamander species (Forester et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Many taxa are known to recognise and respond to chemical stimuli from predators, including reptiles, amphibians, mammals, fish, birds, crustaceans and invertebrates (Kats and Dill 1998;Apfelbach et al 2005). Recognition of predator cues can be threat sensitive, as predicted by the threat-sensitive hypothesis, whereby prey can differentiate between predators based on the degree of threat posed (Helfman 1989;Stapley 2003;Lloyd et al 2009;Cornelis et al 2019). Alternatively, predator recognition can be generalised via avoidance of multiple species cues (Blumstein 2006;Webb et al 2009Webb et al , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in contrast to Landova et al [39], which presented the snake, we only presented the chemical cues and in a different manner to the one used in other studies with scented filtered papers [52][53][54]. However, as Cornelis et al [51] pointed out, it is unclear which method is more effective in capturing appropriate predator odors or which specific chemicals induce the antipredator behavior, and more studies in this area are needed to properly interpret these differences.…”
Section: Discussionmentioning
confidence: 99%
“…According to the threat-sensitivity hypothesis, animals should adjust their anti-predator responses according to the level of threat posed by specific predators, i.e., [49,50]. For example, it has been shown that Asian house geckos (Hemidactylus frenatus) did not respond to the chemical cues of all snakes in the same way [51] or that scincid lizards (Carlia rostralis, C. rubrigularis and C. storri) selectively avoid chemical cues from dangerous varanid predators and ignore those of the less dangerous [52]. Therefore, if our geckos could not distinguish the level of threat or even if the scent represented a threat at all, this could cause the different responses.…”
Section: Discussionmentioning
confidence: 99%
“…The Paradise Flying Snake (Chrysopelea paradisi Boie, 1827) and the Spiny-tailed House Gecko (Hemidactylus frenatus Duméril and Bibron, 1836) are examples of t e first ro p. Hemidactylus frenatus occurs in southeastern Asia and has been introduced to several islands, as well as to Australia, America, and Africa (Das 2010). It is the planet's most widespread lizard, having been spread around the world following human activity (Cornelis et al 2018). This small gecko measures about 67 mm SVL.…”
mentioning
confidence: 99%